2019
DOI: 10.1111/apt.15413
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury is most commonly due to hepatic metastases rather than drug hepatotoxicity during pembrolizumab immunotherapy

Abstract: Summary Background Pembrolizumab immunotherapy has been associated with hepatotoxicity in 1%‐10% of oncology patients treated in clinical trials. Aim To describe the incidence, phenotypes and outcomes of liver injury in a large cohort of solid organ tumour patients receiving pembrolizumab Methods Liver injury was defined by serum alanine aminotransferase, alkaline phosphatase, and/or total bilirubin levels exceeding threshold values. The likelihood of drug‐induced liver injury was adjudicated by expert opinion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 22 publications
(31 reference statements)
4
66
0
Order By: Relevance
“…Among the various toxicities, work-up and management of liver injury is challenging for different reasons [82], including the use of ICIs in hepatocellular carcinoma [83] and chronic hepatitis B infection, as well as the common presence of hepatic metastasis [84,85]. Moreover, the type of liver injury does not affect work-up, whereas thresholds of liver function tests represent the main criteria for diagnosis and relevant management.…”
Section: What's Missing: Managementmentioning
confidence: 99%
“…Among the various toxicities, work-up and management of liver injury is challenging for different reasons [82], including the use of ICIs in hepatocellular carcinoma [83] and chronic hepatitis B infection, as well as the common presence of hepatic metastasis [84,85]. Moreover, the type of liver injury does not affect work-up, whereas thresholds of liver function tests represent the main criteria for diagnosis and relevant management.…”
Section: What's Missing: Managementmentioning
confidence: 99%
“…Within this subset, only 29% of cases, 4.1% of the 491 cases overall, were adjudicated as likely to be drug-related on expert review (i.e., given Drug-Induced Liver Injury Network (DILIN) expert opinion scale scores of 1, definite, 2, highly likely, or 3, probable); most of the remainder were attributed to hepatic involvement by malignancy. The authors suggested an increased emphasis on contrast-enhanced cross-sectional scans and early biopsy in the setting of liver enzyme abnormalities as possible strategies to help reduce diagnostic uncertainty and avoid unnecessary empiric immunosuppression [ 11 ]. Proceeding with such a “prospectively obtained” liver biopsy in our case, where the patient could not undergo contrast-enhanced study due to acute kidney injury, might have expedited diagnosis of diffuse progression, prompting earlier goals of care discussion with the patient and family.…”
Section: Discussionmentioning
confidence: 99%
“…Labs were consistent with a cholestatic pattern of injury ( R = 1.2). Although checkpoint inhibitors are more associated with the hepatocellular pattern of injury, there are multiple case reports of pembrolizumab inducing cholestatic injury, even after a single dose [ 11 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study involving 491 patients treated with pembrolizumab noted 14% of patients with liver injury, a majority of which was attributed to hepatic metastases rather than DILI; those with liver injury had lower tumor response and higher mortality, likely due to more advanced cancer before treatment. Therefore, thorough assessment for other etiologies of liver injury should be completed to not only assist with diagnosis but also with management regarding appropriate use of immunosuppressive therapy …”
Section: Tumor Necrosis Factor Alpha Inhibitorsmentioning
confidence: 99%